Exploring the Relationship between Human and Non-human actors in Cycling Tour of Flores Island - Rachman, Arief F.; Mukminin, Amirul; R.B., Linda Desafitri; Arafah, Willy; Hutagalung, M. Husen; Marzulina, Lenny; Ibarra, Florante P.; Quicho, Rosario F.; Collantes, Leila M.; Arief, Hanief Arief (Dirasat: Human and Social Sciences, 2025)
Objectives: Research aimed to recognize the model contestation between human and non-human actors at the arena of cycling tour in the eastern part of Indonesia in Flores Island. Methods: The research was socio-technical paper, qualitative descriptive method was used to follow the contestation value between cycling tourist and its technical actors during the journey. researchers observed and participated on cycling touring at Flores Island. All participants were Jakarta residents that had different variety of age, gender, occupation and living arrangements. variety of participants ranged in age from 44 to52 years old. total of 1 woman and 4 men were interviewed. Results: findings indicated three stages [Pre-departure cycling tour, En route cycling, and Post-cycling tour] that constructed the field of Actor-Network Theory [ANT], contested human and non-human actors, assemblage of the actors and semiotics were performed in this finding. The use of bicycle as main non-human actors to follow by cycling tourist creating the dynamic and interaction between human actors during cycling. Conclusions: research identifies human and non-human relations within cycling tour, then how the process of relation between actors construct tourism product such as cycling tours. The phrases of human and non-human agents, and sociotechnical were employed to investigate semiotics in their relationship. Values of their experiences and their style in cycling related to motives and type of bicycle. ANT approach described cycling in Flores Island, from departure– to destination or during enroute cycling till finish line, and flying back to their home country.